(untitled) (Research, Society and Development, 2026)
This article aims to analyze the contributions that Digital Technologies and their tools can make to the redefinition of didactics and, consequently, the teaching-learning process. The study addresses the situation of didactics in contemporary education and highlights the need to associate digital resources with teaching practice, with a view to improving student learning and training. The importance of the topic is justified by the urgency of associating technological evolution with teaching practice, in order to meet the desires of a society that is increasingly influenced by and demands technological innovations. Of a qualitative nature, of the bibliographic review type, the research is based on journals, scientific articles, dissertations and theses, which made it possible to explain the importance of integrating technological resources to improve teaching dynamics and knowledge construction.